The premises and the scope of use of tutoring in teaching accounting at a university - the perspective of a student and an academic teacher - Sylwia Agnieszka Krajewska; Anna Agata Stronczek (Jesuit University Ignatianum in Krakow, 2019)
RESEARCH OBJECTIVE: The purpose of the article is to present the premises and the scope of use of academic tutoring in didactics of subjects from the field of accounting. THE RESEARCH PROBLEM AND METHODS: The changing economic reality, the growing expectations with regard to professional qualifications, as well as the assumptions of the Higher Education Law Act imply a search for teaching methods that would make the model of university education more appealing, increase its effectiveness and be a response to the growth in educational aspirations of the youth in Poland. The research methods used to achieve this purpose are literature studies and a diagnostic survey with the use of a questionnaire. THE PROCESS OF ARGUMENTATION: The article first presents the idea science and development tutoring, and then, on the basis of the author's own research, attempts to diagnose the readiness of students and teachers for individualisation of cooperation in teaching subjects from the field of accounting. RESEARCH RESULTS: The results are not generalised beyond the institution where the study was carried out but provide guidelines for other organisations thinking about undertaking activities in the area of personalised education. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The results of the conducted research indicate that we should not be asking whether tutoring should be used to teach accounting at the academic level, but to what extent and how to move on, taking account of legal, organisational and financial limitations, from theoretical considerations to practical implementations.